KEMURNIAN HAKIM ADHOK PADA SISTEM PERADILAN HUBUNGAN INDUSTRIAL DI INDONESIA - Daryono (Qaumiyyah: Jurnal Hukum Tata Negara, 2022)
The purpose of this study is to examine the purity of ad-hoc judges in the Industrial Relations Justice system in Indonesia. This study uses a normative legal research method with a statute and comparative approach. The results of the study show that the position of ad hoc judges as executor of judicial power, who should be free to enforce law and justice, is different from that of ad hoc judges at the Industrial Relations Court whose position is regulated in Law No. 2 of 2004 concerning Industrial Relations Dispute Settlement (UU-PPHI). The position of ad hoc judges at the Industrial Relations Court is tied to each of the proposing organizations, either Workers/Labourers' organizations or employers' organization, which causes the position of an ad hoc Judges, in the industrial relations judicial system to be less independent, due to the requirements of the interests of each proposing organization. In fact, the existence of ad-hoc judges in the judicial system is expected to be able to create a sense of community justice. Abstrak Tujuan studi ini untuk mengkaji Kemurnian Hakim Ad-hoc pada sistem Peradilan Hubungan Industrial di Indonesia. Studi ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan komparatif. Hasil studi menunjukkan bahwa Kedudukan hakim Ad-hoc sebagai pelaksana Kekuasaan Kehakiman, yang seharusnya bebas merdeka dalam menegakan hukum dan keadilan, namun berbeda halnya dengan Hakim Ad hoc pada Pengadilan Hubungan Industrial yang kedudukannya diatur dalam Undang-Undang No. 2 Tahun 2004 tentang Penyelesaian Perselisihan Hubungan Industrial (UU-PPHI), Kedudukan Hakim Ad hoc pada Pengadilan Hubungan Industrial ternyata terikat dengan masing-masing organisasi pengusul, baik organisasi Pekerja/Buruh atau organisasi pengusaha, yang menyebabkan kedudukan Hakim Ad hoc dalam sistem peradilan hubungan industrial menjadi tidak independen, karena syarat kepentingan dari masing-masing organisasi pengusul. Padahal keberadaan hakim ad-hoc pada sistem Peradilan diharapkan mampu menciptakan rasa keadilan masyarakat.